Autonomy and Freedom – Correlation of Concepts in Political and Legal Doctrines - Górecki, Olgierd (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The aim of the article is to present the relation of significance between the concepts of autonomy and freedom in the context of political and legal doctrines. The analysis carried out serves to demonstrate that the concept of autonomy has a narrower meaning, included in a broader category, which is freedom. While the concept of autonomy is not identical with the negative approach to freedom, which boils down to having the widest possible spectrum of alternatives to choose behavior, it is expressed in the concept of positive freedom, which basically means independent control of one’s own behavior. Both concepts were examined only in the context of perceiving them as a human attribute. The methodology of the conducted analysis is based mainly on the concepts of Isaiah Berlin, Gerald C. MacCallum Jr. and Gerald Dworkin. The article also discusses the understanding of the concept of autonomy in selected judgments of the European Court of Human Rights.